3D Printing as an Alternative to Casting, Forging and Machining Technologies? - Fousová, Michaela; Vojtěch, Dalibor; Kubásek, Jiří; Dvorský, Drahomír; Machová, Markéta (Manufacturing Technology Journal, 2015)
3D printing technology has recently extended to metallic materials and allows now to produce 3D models directly from metallic powders. There are several methods of 3D metal printing, such as Selective Laser Sintering (SLS), Direct Metal Laser Sintering (DMLS), Electron beam melting (EBM) or Selective laser melting (SLM). Compared to conventional technologies of casting, forging and machining, these methods offer many advantages. The most important is shape variety allowing preparation of very complicated shapes and designs, which would be impossible to reach by classical techniques. Moreover, there is practically no material loss, since the remaining powder can be recycled and reused in other manufacturing processes. That is one of important cost savings. However, for now, the metal 3D printing is unable to compete the price of large-lot production. In present paper, it is demonstrated that by the SLM technology it is possible to achieve comparable material properties of stainless steel AISI 316L as by conventional technologies and therefore, this method offers a suitable alternative.
Keywords: 3D printing; SLM; AISI 316L; mechanical properties